2002
DOI: 10.1159/000057080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Platelet Concentrates Obtained with Two Different Plateletpheresis Programs of MCS<sup>®</sup>+

Abstract: Background: The new software, revision C2 of the MCS+ (Haemonetics) with continuous filtration provides reduced leukocyte filtration rates of 8–10 ml/min as the collection and storage bags hang in parallel and both are positioned slightly above the level of the leukocyte filter. Filtration is performed during the entire collection procedure. Prolonged active line sensor control enhances the surge mechanism and thus collection efficiency. Return flow rates are adapted to donors’ body weight and observed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Compared to our previous data, PLT yield was higher with the new software revision [7]. The present data are in line with those of Stiegler et al, who reported on a median CE of 68% and a PLT yield 4.11 · 10 11 [27]. CE obtained with the discontinuous flow separator MCS+ are similar to those of the Amicus blood cell separator [5][6][7] and higher than those of the AS.TEC 204 and Cobe Spectra devices [2,3,5].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared to our previous data, PLT yield was higher with the new software revision [7]. The present data are in line with those of Stiegler et al, who reported on a median CE of 68% and a PLT yield 4.11 · 10 11 [27]. CE obtained with the discontinuous flow separator MCS+ are similar to those of the Amicus blood cell separator [5][6][7] and higher than those of the AS.TEC 204 and Cobe Spectra devices [2,3,5].…”
Section: Discussionsupporting
confidence: 91%
“…They concluded that better WBC removal was obtained with continuous filtration than with postcollection filtration. Stiegler and co-workers reported on a significantly lower median WBC contamination of 0.028 · 10 6 in SDPs leukoreduced with a low filtration rate compared with SDPs, which were filtered with a high filtration rate [27]. Our present study confirms these findings as the WBC numbers of the SDPs were lower than in our previous study with postcollection filtration resulting in a mean WBC contamination of 0.088 ± 0.178 · 10 6 [7].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation